2020
DOI: 10.7150/jca.41472
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield and Performance of a Large Population-Based Cervical Cancer Screening Program in High-Risk Rural China

Abstract: Primary cervical cancer screening by liquid-based cytology alone or with adjunctive HPV testing are available worldwide. However, little if any information is available about cervical cancer diagnostic yield of population-based cervical cancer screening in China. In response to it, we conducted a large prospective study on 40,000 women cervical cancer screening within six-month period in rural Shanxi Province, where has been reported as the highest cervical cancer rates in China. A standard cross-sectional sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…We hypothesize that although Guangxi is a developing region with low economic conditions, the regional economic differences among counties in Guangxi are not as large as those reported in previous studies between developed and developing countries. The positive rate of HSIL (0.60%) in Guangxi was higher than that reported in recent studies (0.48%-0.56%) in China [29][30][31] but lower than that reported in other developing counties or areas. 31,32 Notably, this study was based on cervical cytological results rather than histological results, which is similar to some population-based studies on CC screening.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…We hypothesize that although Guangxi is a developing region with low economic conditions, the regional economic differences among counties in Guangxi are not as large as those reported in previous studies between developed and developing countries. The positive rate of HSIL (0.60%) in Guangxi was higher than that reported in recent studies (0.48%-0.56%) in China [29][30][31] but lower than that reported in other developing counties or areas. 31,32 Notably, this study was based on cervical cytological results rather than histological results, which is similar to some population-based studies on CC screening.…”
Section: Discussioncontrasting
confidence: 69%
“…The positive rate of HSIL (0.60%) in Guangxi was higher than that reported in recent studies (0.48%–0.56%) in China 29 – 31 but lower than that reported in other developing counties or areas. 31 , 32 Notably, this study was based on cervical cytological results rather than histological results, which is similar to some population-based studies on CC screening. In this study, we found that being female over 64 and being from an urban area were common risk factors for CC and HSIL.…”
Section: Discussionmentioning
confidence: 84%
“…Cervical intraepithelial neoplasia and cervical cancer are mainly closely related to sexually transmitted high-risk human papillomavirus (HPV) infection, which can cause more than 99% of the incidence of cervical cancer [4]. e current screening methods for cervical cancer mainly include cytology and HPV nucleic acid testing [5]. Conventional cytology and liquid-based thin-layer cell testing (TCT) have high sensitivity and specificity for cervical precancerous lesions; although HPV screening and cytology have the same or better results, the specificity of HPV testing is low.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we speculate that this result may be related to implementation of the CC screening program in China. [53,54] This program targets Chinese women of the appropriate age to detect patients with early CIN in a timely manner and prompt patients with mild disease to seek medical treatment as early as possible; as a result, patients consume fewer medical resources and bear lower treatment costs. [55]…”
Section: Main Findingsmentioning
confidence: 99%